Mer du Nord, Islande et Faeröe / Service hydrographique de la Marine 1922 - France. Service hydrographique de la marine; (1930)
Corrigé 1930 Selected light beacons shown in yellow.; Relief shown by hachures and spot heights. Depths shown by soundings.; Includes correction information in lower left margin Color; 1:167,000